2022
DOI: 10.1007/s10792-022-02244-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the anterior chamber angle by anterior segment optical coherence tomography after implantable phakic contact lens implantation in myopic eyes

Abstract: Purpose To evaluate the changes in the angle of the AC and lens vault after IPCL implantation by AS-OCT in myopic patients. Methods This was a prospective observational study involving 30 myopic eyes implanted with IPCL. AS-OCT was used to evaluate lens vault and AC angle parameters including anterior chamber angle, angle opening distance and trabecular-iris space area (TISA) at 1, 3 and 6 months postoperatively. Results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…After IPCL insertion at 6 months postoperatively, this is consistent with our study findings of ACA500 and AOD500. [20] This was the first study to compare ACA500 and AOD500 after phakic IOL implantation, which has been exclusively addressed in existing literature on glaucoma. [23,31] In our study, we observed a significant decrease in the ACA and AOD parameters at 12 months after surgery compared to before the operation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…After IPCL insertion at 6 months postoperatively, this is consistent with our study findings of ACA500 and AOD500. [20] This was the first study to compare ACA500 and AOD500 after phakic IOL implantation, which has been exclusively addressed in existing literature on glaucoma. [23,31] In our study, we observed a significant decrease in the ACA and AOD parameters at 12 months after surgery compared to before the operation.…”
Section: Discussionmentioning
confidence: 99%
“…After IPCL insertion at 6 months postoperatively, this is consistent with our study findings of ACA500 and AOD500. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Mahmoud et al, implantable phakic contact lens implantation is a safe method for myopia correction, with stable narrowing of the AC (anterior chamber) angle within 6 months after surgery under AS-OCT control [17] . Our patient showed marked narrowing up to 18° in the right eye.…”
Section: Discussionmentioning
confidence: 99%